Analyzing Russian Media Policy on Promoting Vaccination and Other COVID-19 Risk Mitigation Measures - Stepanov, Ivan; Komendantova, Nadejda (Frontiers in Public Health, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has resulted in many tangible and intangible losses. To manage the risk of the pandemic and to mitigate its further spread, governments of many countries applied various pandemic risk mitigation measures. Media campaigns played a particularly large role during the pandemic, too. In addition, social media grew in importance because of the spread of technologies and as a result of the increased attention to information about COVID-19. Media information strongly influenced both the public perception of COVID-19 risk and decision-making processes and choices, which people made regarding risk reduction measures during the pandemic. Moreover, media information has had a major impact on the effectiveness and efficiency of various countries' risk management actions. Therefore, the purpose of this article is to investigate the influence of the Russian media on the population's perception of risk, and to address the question about which linguistic and psychological methods they used to shape different media discourses about the COVID-19 pandemic. Thus, we analyzed media discourses as a part of the case study of COVID-19 risk management in the Russian Federation. The theoretical basis of the study includes mass communication theories. The methodological basis consists of linguo-cognitive analysis of empirical materials for specific political-philosophical, linguistic-publicistic, and sociopsychological functioning.